HUBUNGAN KONSEP DIRI DENGAN INTERAKSI SOSIAL REMAJA PANTI ASUHAN PUTRA MUHAMMADIYAH LABRUK LOR LUMAJANG - khosim, mokhammad; Hidayati, Nura (Dakwah, 2018)
This study discusses the relationship of self-concept and the social interaction of the youth of Muhammadiyah Boys Orphanage, Labruk Lor, Lumajang. This study uses a quantitative approach; the data collection method uses questionnaires, interviews, and documentation. The study uses a population of 21 teenagers at Muhammadiyah Boys Orphanage, Labruk Lor, Lumajang. The results of the Product Moment correlation test shows there is a positive relationship between self-concept and the social interactions of Muhammadiyah Boys Orphanage, Labruk Lor, Lumajang. This is indicated by the correlation coefficient (r) of 0.959 with a significance level of 0.000 <0.05. The conclusion shows the relations between self-concept and the social interaction of the youth of Muhammadiyah Boys Orphanage, Labruk Lor, Lumajang. This means that the higher the self concept of a child, the higher the social interaction. Conversely, if a child's self-concept is low, his/her social interaction becomes lower. Key Words: Self-Concept, Social Interaction, the Youth